Code name Sapphire [large type] - Jenoff, Pam (Thorndike Press large print core series., 2023)
"1942. Hannah Martel has narrowly escaped Nazi Germany. When her ship bound for America is turned away at port, she has nowhere to go but to her cousin Lily in Brussels. Fearful for her life, Hannah is desperate to get out of occupied Europe. But with no safe way to leave, she must return to the dangerous underground work she thought she had left behind. Seeking help, Hannah joins the Sapphire Line, a secret resistance network. But when a grave mistake causes Lily's family to be arrested and slated for deportation to Auschwitz, Hannah finds herself torn between her loyalties. How much is Hannah willing to sacrifice to save the people she loves?"--